ANALISIS PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON ASSET TEHADAP DIVIDENT PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Mufidah, Mufidah; Khoirunnisa, Rikha Muftia (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to determine the effect of cash position, debt to equity ratio, and return on assets to the dividend payout ratio of the company automotive manufacturing sector, food and beverage sector, cigarette sector, sector ceramics, cement sector, cable sector and electronics sector which are listed on the Exchange Indonesian Securities 2012-2014 period. The sample in this study is manufacturing companies, automotive sector, food and beverage sector, sector cigarette, ceramic sector, cement sector, cable sector and electronics sector. Technique sampling using purposive sampling technique obtained 17 the sample. Hypothesis test results using multiple linear regression showed that partially cash position and return on assets affect dividend payout ratio, while the debt to equity ratio has no effect on dividend payout ratio, while simultaneous cash positions, debt to equity andreturn on assets affects the dividend payout ratio.